Kenya's Tourism : Polishing the Jewel - World Bank (Washington, Dc, 2013)
Kenya's tourism product lines and its source markets function in a cross-sectoral context, which leads to cross-cutting public and private sector issues. Tourism has played a major role in Kenya's development despite economic jolts from time-to-time by internal and external shocks. In 2006 and 2007 the economy grew rapidly and tourism, after a jolt in early 2008, rebounded thanks to market conditions and some solid marketing. The global recession, of course, has since intervened, and Kenya will have to continue with bold and committed actions if it is to regain its iconic position in world tourism. Value chain analysis of safari, coastal, and business and conference tourism highlights constraints and opportunities. Current tourism enterprises are hampered by significant taxation and regulation. Peaks and valleys in tourism flows have exacerbated already limited access to capital necessary for the sector to be competitive. The key to sustainability lies in Kenya's ability to provide a mix of tourism products -safari, coastal, cultural/heritage and business and conference - while protecting the very assets these products celebrate.